Professional Counselors’ Experiences Counseling and Working in Areas Repeatedly Impacted by Hurricanes - Sarah Krennerich; Maria Haiyasoso; Paulina S Flasch (Teaching and Supervision in Counseling, 2021)
Previous research on professional counselors’ lived experiences of disaster counseling has focused mainly on single disasters. Researchers have identified a need to explore further the phenomenon of post-disaster counseling and shared trauma between counselors and clients. In this article, the authors sought to answer the following research question: What are the lived experiences of professional counselors who live and facilitate post-disaster counseling in areas repeatedly affected by hurricanes along the Texas Gulf Coast? The authors describe their phenomenological study of licensed professional counselors (n = 6) who lived and worked in areas repeatedly impacted by hurricanes along the Texas Gulf Coast. Implications for counselors, counselor educators, and supervisors are provided.
Keywords: repeated disasters; post-disaster; counseling; disaster counseling training; shared trauma